Гайдар на Севере - Бурлов Александр Николаевич (Северо-Западное книжное издательство, 1973)
Экземпляры: КХ (20121219) / Инвентарный номер: 0217863 / Цена: 0.15 / Сис.шифр: 8Р2 / Авт.знак: Б 91 / ГРНТИ: 17 / ББК: 83